Estimation of Gestational Age by Using Fetal Kidney Length in Comparison with Other Biometric Indices - Sushmitha Alias Tulasi; R Sarvesh; T Shriram (Journal of Pharmacy and Bioallied Sciences)
Background: Fetal kidney length (FKL) has emerged as a promising alternative, with a strong correlation to gestational age, particularly in the third trimester. Aim: To determine the accuracy of FKL in estimating fetal gestational age by ultrasonography and comparing its efficacy with other biometric indices. Materials and Methods: A comparative observational study was conducted at Aarupadai Veedu Medical College and Hospital, Puducherry, involving 110 antenatal women with singleton pregnancies between 20 and 40 weeks of gestation. Ultrasound examinations were performed using a Mindray DC 80 machine with a 3.5-5 MHz curvilinear probe. Gestational age was estimated using FKL and compared with standard biometric indices. Pearson correlation analysis and independent t-tests were performed using SPSS version 26.0, with significance set at P < 0.05. Results: A significant positive correlation was observed between FKL and gestational age (r = 0.975, P < 0.001). The mean FKL showed a consistent linear increase with advancing gestational age, comparable to traditional biometric indices such as head circumference and abdominal circumference. Right and left kidney lengths exhibited similar correlations, reinforcing the reliability of FKL in estimating gestational age. Conclusion: FKL is a reliable parameter for gestational age estimation, particularly in the third trimester. Its strong correlation with standard biometric indices supports its use as an adjunct in prenatal ultrasound assessments, especially in cases where conventional measurements are inconclusive.